Following Baxter - Kerley, Barbara (Harper, an imprint of HarperCollinsPublishers, 2018)
When Professor Reese moves in next door, eleven-year-old Jordie enjoys helping her new neighbor take care of her dog and assisting in her laboratory, but she is not sure what to do when the professor goes missing.